Classifying Prosocial Behavior: Children's Responses to Instrumental Need, Emotional Distress, and Material Desire. Issue 5 (5th March 2013) - Dunfield, Kristen A.; Kuhlmeier, Valerie A.
Abstract : This study investigates the diversity of early prosocial behavior by examining the ability of ninety‐five 2‐ to 4‐year‐olds to provide aid to an adult experimenter displaying instrumental need, emotional distress, and material desire. Children provided appropriate aid in response to each of these cues with high consistency over multiple trials. In contrast to the consistency with which the children provided aid within each task, there were no cross‐task correlations, and the tendency to respond to each of the cues revealed unique developmental trajectories. Taken together, these results provide preliminary support for the importance of examining the cues to which children are responding and of differentiating between varieties of aid when considering the development of prosocial behavior.